Toward sustainable transformation through postharvest management: Lessons from Kenya's mango value chain - Ambuko, Jane; Owino, Willis (International Food Policy Research Institute, 2023)
Management of postharvest food loss and waste (FLW) is an important strategy in efforts to sustainably meet the food and nutrition needs of the world’s growing population. Sustainable food systems are critical to achieving food security and nutrition for all, now and in the future. Food systems cannot be sustainable when a large proportion of the food produced using limited resources is lost or wasted in the supply chain. At the global level, it is estimated that poor postharvest management means this is the case for 30 percent of the food produced for human consumption (FAO 2011, 2019).